Novel Laplace-domain Approach to the Electromagnetic Transients in Compensated High Voltage Power Lines - Mohamed M. Saied (International Journal of Electrical Machine Analysis and Design, 2024)
This paper addresses the simulation of the electromagnetic transients developed in high voltage power lines, which are initiated by lightning discharges. The analysis can handle both individual and simultaneous series inductive and shunt capacitive compensation types. The sizes and locations of the compensating elements are included in the analysis. The derived Laplace s-domain mathematical model applies the concept of the ABCD transmission constants representing equivalent two-port networks. Applying the relations governing cascaded two-port networks, the resulting branch currents and node voltages will be obtained as functions of the location of the compensating elements, the line’s data as well as the Laplace operators. An efficient Mathematica code based on the Hosono algorithm is used for their numerical inversion in order to get the corresponding results in the time domain. The model and computer code are validated via discussing the results of their application to several case studies with solutions available elsewhere.
Keywords: Compensation; Simulation; Validation; electromagnetic; high voltage lines; mathematica; numerical Laplace inversion. Hosono algorithm; parallel; parameter study; series; transients; two-port networks